2014
DOI: 10.1266/ggs.89.51
|View full text |Cite
|
Sign up to set email alerts
|

AbpA and AbpB provide anti-phage activity in <i>Escherichia coli</i>

Abstract: Bacteria have a variety of resistance mechanisms for surviving bacteriophage infections. Here, we describe a novel anti-phage mechanism in Escherichia coli. Cells harboring a plasmid with the genes abpA and abpB, formerly yfjL and yfjK, blocked the propagation of bacteriophages belonging to three families: T4, T2, T7 and λ phages. Both genes were necessary for the inhibition of phage propagation, and deletion of either chromosomal gene resulted in a 20% increase of progeny compared to wild-type cells. Neither … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Such mutations allowed phages to escape the systems Lamassu, Hachiman, ietAS , Retron-Eco8, ShosTA, Borvo, and some AVAST systems (Figure 3, Figure 6). Previous studies on the anti-phage defense systems AbiK (Bouchard and Moineau, 2004; Wang et al, 2011), AbiQ (Samson et al, 2013b), ApbA/B (Yasui et al, 2014), DarTG (LeRoux et al, 2022), Tin (Mosig et al, 1997), and Nhi (Bari et al, 2022) have also reported phage escape via mutation in one of these core replication proteins. Thus, diverse defense systems have evolved to sense or target the core determinants of phage replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mutations allowed phages to escape the systems Lamassu, Hachiman, ietAS , Retron-Eco8, ShosTA, Borvo, and some AVAST systems (Figure 3, Figure 6). Previous studies on the anti-phage defense systems AbiK (Bouchard and Moineau, 2004; Wang et al, 2011), AbiQ (Samson et al, 2013b), ApbA/B (Yasui et al, 2014), DarTG (LeRoux et al, 2022), Tin (Mosig et al, 1997), and Nhi (Bari et al, 2022) have also reported phage escape via mutation in one of these core replication proteins. Thus, diverse defense systems have evolved to sense or target the core determinants of phage replication.…”
Section: Resultsmentioning
confidence: 99%
“…Although our understanding of bacterial immunity has substantially expanded by these recent discoveries, for the vast majority of the defense systems it is still unknown how they recognize invading phages, and this remains a major unanswered question in the field. Previous studies on individual defense systems, have addressed this question by examining phage mutants that escape defense (Bari et al, 2022;Depardieu et al, 2016;Huiting et al, 2022;Millman et al, 2020;Samson et al, 2013a;Tal et al, 2021Tal et al, , 2022Yasui et al, 2014). Such phages sometimes evade bacterial immunity by mutations in phage components that activate the bacterial defense system; thus escape mutants can generate valuable insights into the mechanism of defense activation (Samson et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…1A ). AbpA and AbpB (AbpAB) coexpression suppresses the growth of many lytic phages harboring double-stranded DNA (dsDNA) genomes ( 14 ). AbpA and AbpB physically interact for phage defense.…”
Section: Introductionmentioning
confidence: 99%
“…AbpAB is activated after the middle stage of infection and inhibits DNA replication in T2, T4, and T7 phages. However, the T4 phage can evade the AbpAB defense system through a mutation in gene 41, which encodes a replicative DNA helicase ( 14 , 15 ). However, the function of Gp41 in this system, the AbpAB activation mechanism after phage infection, and how AbpAB inhibits phage propagation remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The AbpAB antiphage defense system was described before the identification of Hachiman 62 . AbpAB encodes a nuclease (AbpA) and a Ski2-like helicase (AbpB) with combined activity against DNA.…”
Section: Discussionmentioning
confidence: 99%